Prevalence and predictors of sexual victimization among incarcerated men and women in Spanish prisons - Caravaca-Sánchez, Francisco (Criminal justice and behavior, 2016)
Little is known about the prevalence of sexual victimization (SV) in prisons located outside the United States or the relationship between SV and current substance use (SU) among incarcerated persons. This study explores the prevalence of SV inside Spanish prisons and the association between SV and SU experience based on data collected from a sample of inmates aged 18 or older (N = 2,709) located in eight prisons in the southeast of Spain. The estimated prevalence of SV over a 6-month period was 6.6%, with higher rates for females (12.0%) than men (6.1%). SU while incarcerated and history of childhood SV were significantly correlated with SV inside prison. This evidence suggests the need for integrated SU and trauma treatment, along with strong prevention interventions to reduce the risk of SV among inmates in Spanish prisons.